2017
DOI: 10.1016/j.matdes.2017.05.077
|View full text |Cite
|
Sign up to set email alerts
|

Process-induced bottom defects in clinch forming: Simulation and effect on the structural integrity of single shear lap specimens

Abstract: Lightweight and high strength sheet metal such as aluminium alloy sheets are used in a variety of industrial applications. Due to the limited weldability of these materials, mechanical joining techniques such as clinching are of interest. The challenge in this regard is that conventional round clinch forming locally induces large plastic deformations which potentially cannot be accommodated by materials with limited ductility. Ductile damage models are used to predict the occurrence of bottom cracks during con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…For the geometrical analysis of a clinch element, photographs or micrographs of cross-sections are evaluated conventionally (cf. [ 9 , 24 , 25 ]). These methods have the disadvantage that the joining zone can only be evaluated in one section plane and thus three-dimensional phenomena, such as fibre reorientations, can hardly be evaluated.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…For the geometrical analysis of a clinch element, photographs or micrographs of cross-sections are evaluated conventionally (cf. [ 9 , 24 , 25 ]). These methods have the disadvantage that the joining zone can only be evaluated in one section plane and thus three-dimensional phenomena, such as fibre reorientations, can hardly be evaluated.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Reducing the embossment thickness increases the joint strength; however, it is connected with increasing the forming force. Coppieters et al [11] studied the bottom defects that were generated while creating the permanent interlock in the case of clinching with a rigid die. The study shows that the observed bottom cracks can be predicted by means of the axisymmetric FE model while using the modified Rousselier model.…”
Section: Introductionmentioning
confidence: 99%
“…This modified damage model can describe the evolution of the fracture with the initial void volume fraction and the shear damage parameter. Coppieters et al [ 15 ] used a modified Rousselier damage model [ 14 ] to describe the fracture behavior in the bottom of the clinched joint under overload. Lambiase and Di Ilio [ 16 ] explored a numerical model that describes the evolution of ductile damage in predicting the onset of fracture during the clinch joining of thin aluminum AA6082-T6 sheets.…”
Section: Introductionmentioning
confidence: 99%